Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Israel
Keywords: 2023-10 November

Cambodia: Mass evictions at UNESCO World Heritage site Angkor violate international law - Amnesty International (Amnesty International, 2023)
Cambodian authorities cruelly uprooted families who have lived in Angkor for several generations.
Cambodia
Keywords: 2023-10 November

Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Palestine (permanent observer to the UN)
Keywords: 2023-10 November

South Korea: Jail sentence for man who praised North an attack on freedom of expression - Amnesty International (Amnesty International, 2023)
Responding to the sentencing of a South Korean man, Lee Yoon-seop, to 14 months in prison for praising North Korea in a poem, Amnesty International’s East Asia Researcher Boram Jang said: “South Korean authorities must drop all charges against Lee Yoon-seop, who has been sentenced to jail simply for exercising his right to freedom of […]
Korea, Republic of
Keywords: 2023-10 November; Republic of Korea